The Politics and Analytics of Health Policy - Calum R. Paton (Kerman University of Medical Sciences, 2014)
Let us start with an example of health policy analysis in action. Within that category of countries loosely known as 'the West', quite basic differences exist in attitudes to health policy and also actual health policy. Comparing the US with mainland Europe and indeed Canada, for example, one perceives a difference in attitude on the part of the majority towards collectivism and individualism in access to, provision of and financing of healthcare. The explanation for policy and system differences-for example, between the US healthcare system(s) and the various NHSs of the UK countries (England, Scotland, Wales and Northern Ireland)-is commonly framed in terms of 'ideology' but there are also 'institutional' explanations (1). Additionally, however, popular attitudes or 'values' may be taken as autonomous 'inputs' into the explanation (e.g. 'American values prevent the enactment of an NHS') or, at least in part, derived from or influenced by institutional reality. If, for example, there is no chance of a bill to establish an NHS or a comprehensive system of public health insurance passing in Washington, then reformers over time trim not only their legislative ambitions, but also their very way of thinking about the issue.